Factors associated with smoking and e-cigarette use statuses among individuals with chronic diseases after hurricanes Helene and Milton - Francis Dalisay; Young-Rock Hong; Haoran Chu; Ramzi G. Salloum (Tobacco Induced Diseases, 2025)
Introduction Natural disasters increase health risks for individuals with chronic diseases and may worsen substance use behaviors as a coping mechanism. The present study examined post-disaster intentions to use and past 30-day use of cigarettes and e-cigarettes and associated factors among individuals with chronic diseases who experienced hurricanes Helene and Milton.